Ab Initio Investigation of the Microspecies and Energy in Hydrated Strontium Ion Clusters. (17th January 2018) - Zhu, Fayan; Zhou, Hongxia; Fang, Chunhui; Fang, Yan; Zhou, Yongquan; Liu, Hongyan
ABSTRACT: Quantum chemistry calculations were used to study the structure and energy of strontium (Sr) ion hydrated clusters [Sr(H2 O)1−25 ] 2+ . The saturated hydration number of the first hydration layer of Sr 2+ was 8, and the hydration distance was 2.58 Å. The second hydration layer had 1–9 hydration numbers, and the hydration distance was in the range of 4.4–4.6 Å. This work also developed the relationship between the thermodynamic data (average water binding energy En and successive water binding energy Δ En, n −1, etc.) of the aforementioned low-energy structure and the hydration structures. The first hydration layer was formed by the strong electrostatic interaction between Sr 2+ and water molecules, and the decrease in Δ En, n −1 was relatively large. Hydrogen bonds were formed between water molecules of the second hydration layer and water molecules of the inner layer, and the decrease in Δ En, n −1 was relatively small. When one water molecule was added beyond the second hydration layer, Δ En, n −1 was close to the hydrogen bond energy 8.88 kcal/mol (37.1 kJ/mol) of dimer water molecule, indicating that there was very weak interaction between Sr 2+ and the water molecules beyond the second hydration layer. Abstract :